Changing views of teachers and teaching in Vietnam. Issue 3 (3rd July 2017) - Nguyen Thi Mai, Huong; Hall, Christine
Abstract: In order for Vietnam to seek better international integration into an increasingly globalised world, the Vietnamese Government has launched educational reforms requiring teachers to adopt 'Western' constructivist pedagogies. This paper reports on an action research study in a Vietnamese teacher training institution which found that Vietnamese student teachers were willing to accommodate and accept change and were often very enthusiastic about the 'Western ideas' of teaching and learning, but that their unquestioning respect for the authority of their tutors remained firmly fixed. The data also showed that the students' tutors had a relatively limited exposure to the 'Western theories' and their implications and therefore did not model or demonstrate the theories effectively. The paper draws on these findings to argue that the focus for transforming Vietnamese teachers' practice should be on promoting the responsibility of teacher educators to introduce student teachers to new ideas about the processes of teaching and learning. This strategy is likely to be more supportive of student teachers' development as it allows them to separate the processes of teaching from culturally dominant beliefs about roles which are part of their established identities.